The Impact of Hyaluronan on Tumor Progression in Cutaneous Melanoma - Takabe, Piia; Siiskonen, Hanna; Rönkä, Aino; Kainulainen, Kirsi; Pasonen-Seppänen, Sanna (Frontiers in Oncology, 2022)
The incidence of cutaneous melanoma is rapidly increasing worldwide. Cutaneous melanoma is an aggressive type of skin cancer, which originates from malignant transformation of pigment producing melanocytes. The main risk factor for melanoma is ultraviolet (UV) radiation, and thus it often arises from highly sun-exposed skin areas and is characterized by a high mutational burden. In addition to melanoma-associated mutations such as BRAF, NRAS, PTEN and cell cycle regulators, the expansion of melanoma is affected by the extracellular matrix surrounding the tumor together with immune cells. In the early phases of the disease, hyaluronan is the major matrix component in cutaneous melanoma microenvironment. It is a high-molecular weight polysaccharide involved in several physiological and pathological processes. Hyaluronan is involved in the inflammatory reactions associated with UV radiation but its role in melanomagenesis is still unclear. Although abundant hyaluronan surrounds epidermal and dermal cells in normal skin and benign nevi, its content is further elevated in dysplastic lesions and local tumors. At this stage hyaluronan matrix may act as a protective barrier against melanoma progression, or alternatively against immune cell attack. While in advanced melanoma, the content of hyaluronan decreases due to altered synthesis and degradation, and this correlates with poor prognosis. This review focuses on hyaluronan matrix in cutaneous melanoma and how the changes in hyaluronan metabolism affect the progression of melanoma.